5m+6km-8hm=

Simple and best practice solution for 5m+6km-8hm= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5m+6km-8hm= equation:


Simplifying
5m + 6km + -8hm = 0

Reorder the terms:
-8hm + 6km + 5m = 0

Solving
-8hm + 6km + 5m = 0

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-6km' to each side of the equation.
-8hm + 6km + -6km + 5m = 0 + -6km

Combine like terms: 6km + -6km = 0
-8hm + 0 + 5m = 0 + -6km
-8hm + 5m = 0 + -6km
Remove the zero:
-8hm + 5m = -6km

Add '-5m' to each side of the equation.
-8hm + 5m + -5m = -6km + -5m

Combine like terms: 5m + -5m = 0
-8hm + 0 = -6km + -5m
-8hm = -6km + -5m

Divide each side by '-8m'.
h = 0.75k + 0.625

Simplifying
h = 0.75k + 0.625

Reorder the terms:
h = 0.625 + 0.75k

See similar equations:

| =i^103 | | 4s^2-8=0 | | .66y=12 | | 24=-.33t | | .20n=-9 | | 4s^2-3s=0 | | 3(x^2-14x+49)=-14 | | 9s^2+2s-9=0 | | 3s^2-9s-6=0 | | 6(1+2x)-(8x-7)=17 | | w-11=3 | | 2(x)-8=x-7 | | 5v+25= | | 5(15x+5)=415 | | cos(x)=11x | | 7x^2+5x+h=0 | | ln(x+35)-ln(x-1)=ln(x-5) | | 6s^2+5s=0 | | 2+10(4x+5)= | | 3(x^2-14x)=-14 | | 6(-3x+4)=-120 | | .2x+.3y=.23(100) | | 5s^2-5s-7=0 | | -2s-7=5 | | 8s^2-6s-8=0 | | 48=x(16-x) | | 5w-7w+6+8w= | | 2s^2-3s+8=0 | | 4s+4=-28 | | 2s^2-6s+2=0 | | 6s^2-7s+1=0 | | Log^3(3-5x)=2 |

Equations solver categories